Measures of Heart Rate Variability in 24-h ECGs Depend on Age but Not Gender of Healthy Children - Bobkowski, Waldemar; Stefaniak, Magdalena E.; Krauze, Tomasz; Gendera, Katarzyna; Wykretowicz, Andrzej; Piskorski, Jaroslaw; Guzik, Przemyslaw (Frontiers in Physiology, 2017)
Many methods computing heart rate variability (HRV) have been applied in studies in children. Not all of these methods have a comprehensive physiological interpretation, and not all of studies are in agreement with the Task Force Standards on HRV from 1996, and the New Joint Position Statement on the advances of HRV from 2015. The study aim was to analyse HRV in the 24-hour ECGs of healthy children by the Poincare plots and Lomb-Scargle periodograms, and to follow proper HRV recommendations. Additionally, we investigated the associations between age, children’s sex and measured HRV indices. One hundred healthy children, aged 3-18 underwent 24-hour ECG Holter monitoring. HRV was analysed by the Poincaré plots and spectral by Lomb-Scargle periodograms of RR intervals. The Mann-Whitney test was used to compare sex differences in HRV, the van Elteren's test was used to correct for the age-gender interaction, and nonparametric Spearman correlation was applied to analyse the association between age and HRV indices. None of the HRV measures differed significantly between boys and girls. None of the HRV indices was modified by the age-gender interaction. There were statistically significant associations of age with measures of ultra low (rho=0.42; p<0.0001), very low (rho=0.35; p=00004) and low (rho=0.30; p=0.0028) frequency powers, the ratio of the low to high frequency power (rho=0.38; p=0.0001), indices of long-term (SD2; rho=0.37; p=0.0002) and total (SDNN; rho=0.33; p=0.0008) HRV, and the contribution of the long-term HRV to total HRV (CL; rho=0.32; p=0.0012). In general, HRV parameters derived from the analyses of Poincaré plots and Lomb-Scargle periodograms appear not to be affected by gender, however, most of them increase with age in the 24-hour ECG recordings in healthy children.